Клинико-топографическое описание соотношения апексов зубов и дна гайморовой пазухи как анатомический аспект классификации одонтогенных гайморитов (Эндодонтия Today)
There are several classifications of odontogenic sinusitis, which are based on objective and subjective symptoms detected by a doctor after suffering from treatment for medical attention. The importance of clinical-topographical correlation «bottom of the maxillary sinus - posterior teeth apices» indicates all the investigators, but the qualitative features of this aspect in the available literature we found. The paper presents a version of the clinical-topographic description of the relations apex of teeth and the bottom of the maxillary sinus.